Local Wisdom of Traditional Acehnese House Architecture Teungku Chik Awe Geutah XIII Century as an Attraction for Cultural Tourism Objects in Aceh - Novalita, Rahmi; Dewi, Silvi Listia; Zuraihan, Zuraihan; Zahara, Zahara; Ifwadi, Ifwadi; Anshar, Alya Ledias (Universitas Negeri Medan, 2023)
This study describes the local wisdom of Aceh's traditional house architecture and the potential for developing cultural tourism objects. This research method uses a qualitative approach. The research location is Awe Geutah Village, Peusangan Siblah Krueng District, Bireuen District, Aceh Province. The research informants are key informants, namely the managers of Acehnese traditional houses. This study also uses the principles of documentation, inventory, and tourism approaches”data analysis using data reduction, data display, and data reduction. The research results and the research update are the design of the Teungku Chik Awe Geutah Aceh traditional house model. This traditional Aceh house was built around the XIII century and has local wisdom in building construction that is sturdy and earthquake-resistant. The house plan consists of 3 parts: the front, middle, and rear. Each element in the traditional Aceh house has a philosophical meaning and a way of life for the people of Aceh. The potential for developing traditional Aceh houses is viewed from facilities and infrastructure, accommodation, accessibility, transportation, security, and hospitality. Keywords: Architecture, Local Wisdom, Cultural Tourism, Aceh House